Organic compost and potassium top dressing fertilization on production and quality of beetroot - Magro, Felipe Oliveira [UNESP]; da Silva, Ewerton Gasparetto [UNESP]; Takata, William Hiroshi Suekane [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Evangelista, Regina Marta [UNESP] (My University, 2015)
The potassium (K) in top dressing fertilization is used for beetroot production in Brazil. However, most of K studies are made with fertilization before planting, and it is not known the real need of this K top dressing after fertilization with K and organic matter before planting. So this work aimed to evaluate the production and quality of beetroot under different rates of organic compost at planting and K top dressing fertilization. The experiment was carried out in São Manuel-SP, Brazil, with ten treatments (5 x 2 factorial scheme), in a randomized blocks experimental design, with four replications. Five rates (0, 20, 40, 60 and 80 t ha-1) of organic compost applied at planting, in the presence (60 kg ha-1 of K2O) or absence of K top dressing fertilization were evaluated. The traits related to production evaluated were: average weight, diameter and length of roots, yield and K content in shoot and root. For the physicochemical quality of roots, pH, soluble solid content, titratable acidity, index ratio, texture, reducing, non-reducing and total sugar were evaluated. The K top dressing fertilization did not affect the production traits; however, it increases the contents of K in shoot and root and the contents of non-reducing and total sugars. The rates of the compost do not affect the quality traits, but the rate of 49 t ha-1 resulted in the maximum root yield estimated in 43 t ha-1 of roots.
Keywords: Beta vulgaris; Organic fertilization; Soluble solid content; Sugars; Yield